Body approach with tuberculosis: the client's imagination in the care of occupational therapy (Research, Society and Development, 2020)
Objective: analyze how pulmonary tuberculosis patients figure the taking care of their bodies after the diagnosis of the disease. Method: the method used in this investigation was socio-poetic-qualitative. The context chosen was the tuberculosis clinic of a university hospital located in the city of Rio de Janeiro, where they are treated. The strategy for data production involves collective meetings with patients, and decisions were made and approved in the research group's workshops, where collective discussions and the imaginary about body and care. Results: 35 images and 71 spaces were produced. This body changed expression and space, making a counterpoint with the healthy body. It stands out as main areas of order Surrealist socio-poetic study: Well – Labyrinth – Tunnel – Hospital. Conclusion: the tuberculosis patients suffered several assemblages and indicate themes for the care of occupational therapy brings strange combinations in the group's thoughts, causing multiplication of views about the meaning of the sick body.